Optimizing vitiligo treatment: examining the role of narrow-band ultraviolet B phototherapy - Díaz De Alba, Paola Scarlett; Sierra Franco, Andrea; Millán Montaño, María Daniela; García García, Aurora Guadalupe; Ramírez Cortes, Narda Carolina; Hernandez Vespero, Fernando (International Journal of Research in Medical Sciences, 2023)
Vitiligo is a common autoimmune-pigment disorder associated with skin depigmentation. Narrow-band ultraviolet B phototherapy (NB-UVB) has become an effective treatment option for this disease, resulting in significant pigmentation in patients, especially those with facial lesions and dark skin tones. However, the best treatment plan is still under discussion, and more research is needed to assess long-term safety, including the risk of skin cancer. In addition, alternative options such as current immunomodulators and herbal therapies are promising but need further studies. This study reviewed the existing literature on NB-UVB phototherapy's efficacy and safety profile for treating vitiligo. The study focused on factors affecting the treatment response and the potential benefits of combining NB-UVB with other treatments. NB-UVB phototherapy is safe and effectively reduces depigmentation in vitiligo patients. Factors such as disease duration, skin type, and scope of vitiligo lesions may influence treatment results. Using NB-UVB with other treatments can increase results. Although UVB NB phototherapy is a safe and effective option for vitiligo treatment, more research is needed to optimize its use and improve treatment outcomes, especially in different patient groups.